GAMBARAN FAKTOR YANG MEMPERNGARUHI PENERIMAAN DIRI ORANGTUA YANG MEMILIKI ANAK AUTISME - Selvi Selvi; Shanty Sudarji (Universitas Bunda Mulia, 2017)
People with autism has problems such as talking and understanding, and usually they have difficulty interacting with others and the environment. When they were diagnosed with autism, they will have feelings of shock, sadness, worry, embarrassment and fear. To be able to accept the state of autism children needed self-acceptance, This research can be done to determine what factors that can affect a person. This method uses qualitative method of phenomenology type with observation method and result to collect data. The study was conducted on five parents who have children with autism, where children and parents live together. The results of this study can be concluded that factors that are not owned by the subject K is the pattern of care in childhood is good, the effect of success experienced. Factors that Subject D does not have are obstacles in the environment, the impact of success experienced, the self-concept is stable. Factors that are not owned by H is the effect of success experienced, the pattern of foster in childhood is good, stable self-concept. Factors that are not owned by N is the influence of success that occurs and the pattern of foster in good times are good. While T has fulfilled all ten factors. Keywords: Autism, Factors that influence self-acceptance, Parents